Differential requirement for de novo lipogenesis in cholangiocarcinoma and hepatocellular carcinoma of mice and humans. Issue 6 (25th March 2016) - Li, Lei; Che, Li; Tharp, Kevin M.; Park, Hyo‐Min; Pilo, Maria G.; Cao, Dan; Cigliano, Antonio; Latte, Gavinella; Xu, Zhong; Ribback, Silvia; Dombrowski, Frank; Evert, Matthias; et al.
Abstract : Hepatocellular carcinoma (HCC) and intrahepatic cholangiocarcinoma (ICC) are the most prevalent types of primary liver cancer. These malignancies have limited treatment options, resulting in poor patient outcomes. Metabolism reprogramming, including increased de novo lipogenesis, is one of the hallmarks of cancer. Fatty acid synthase (FASN) catalyzes the de novo synthesis of long‐chain fatty acids from acetyl‐coenzyme A and malonyl‐coenzyme A. Increased FASN expression has been reported in multiple tumor types, and inhibition of FASN expression has been shown to have tumor‐suppressing activity. Intriguingly, we found that while FASN is up‐regulated in human HCC samples, its expression is frequently low in human ICC specimens. Similar results were observed in mouse ICC models induced by different oncogenes. Ablating FASN in the mouse liver did not affect activated AKT and Notch (AKT/Notch intracellular domain 1) induced ICC formation in vivo . Furthermore, while both HCC and ICC lesions develop in mice following hydrodynamic injection of AKT and neuroblastoma Ras viral oncogene homolog oncogenes (AKT/Ras), deletion of FASN in AKT/Ras mice triggered the development almost exclusively of ICCs. In the absence of FASN, ICC cells might receive lipids for membrane synthesis through exogenous fatty acid uptake. In accordance with the latter hypothesis, ICC cells displayed high expression of fatty acid uptake‐related proteins and robust long‐chain fatty acid uptake. Conclusion: Our data demonstrate that FASN dependence is not a universal feature of liver tumors: while HCC development is highly dependent of FASN and its mediated lipogenesis, ICC tumorigenesis can be insensitive to FASN deprivation; our study supports novel therapeutic approaches to treat this pernicious tumor type with the inhibition of exogenous fatty acid uptake . (Hepatology 2016;63:1900‐1913)